2019
DOI: 10.1139/cjfas-2017-0453
|View full text |Cite
|
Sign up to set email alerts
|

Influence of baffles on upstream passage of brook trout and brown trout in an experimental box culvert

Abstract: There is much to learn about improving baffle designs to increase successful fish passage through culverts. A fish’s motivation to attempt entry into the culvert is essential. Upon entry, successful passage will largely depend on the physiological ability of the fish to navigate the entire culvert length. In this study, the motivation of brook trout (Salvelinus fontinalis (Mitchill, 1814)) and brown trout (Salmo trutta Linnaeus, 1758) to attempt ascent of an experimental flume, which mimics a roadway culvert l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Thus, fish must search for the equilibrium of the hydraulic conditions to successfully negotiate the obstacle. Specialized references recommend a water depth higher than 20 cm for suitable swimming [15,45], though in velocity barriers tests with Iberian barbel [46][47][48], it was shown that water depths near 10 cm permitted them to develop burst swimming mode with a fork length (FL) lower than 25 cm. In the case of flow velocity, distance traveled by Iberian barbel was reported to be almost halved from 2.5 to 3 m/s [49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, fish must search for the equilibrium of the hydraulic conditions to successfully negotiate the obstacle. Specialized references recommend a water depth higher than 20 cm for suitable swimming [15,45], though in velocity barriers tests with Iberian barbel [46][47][48], it was shown that water depths near 10 cm permitted them to develop burst swimming mode with a fork length (FL) lower than 25 cm. In the case of flow velocity, distance traveled by Iberian barbel was reported to be almost halved from 2.5 to 3 m/s [49].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it should be noted that swimming requirements are great even under the most favorable conditions. These findings are of interest to quantify flat-V weir impacts, for engineering applications and to establish retrofitting actions (such as backwatering [9,11] or increasing roughness over the face by means of baffles or bristle clusters [44,48], among others) when required.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the energy‐saving strategy of fish in unsteady flow is important, with many potential applications across the fields of fisheries science, ecology and fluid dynamics (Duguay et al, 2018; Hockley, Wilson, Brew, & Cable, 2014; Li et al, 2017). Here, we have demonstrated that a combination of obstacles and flow velocity may be beneficial for fish swimming in unstable flow.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is vital to understand the fundamental principles of how fish swim, there are many challenges associated with describing locomotion in natural environments. Recently, a large number of studies have used experimental flumes in the laboratory to stimulate natural flow fields and to examine swimming behaviors of fish (Duguay, Lacey, & Castro‐Santos, 2018; Goettel, Atkinson, & Bennett, 2015; Li, Sun, Liu, & Zheng, 2021; Rodgers, Heaslip, & Cramp, 2017). Goettel et al (2015) assessed the behavioral responses of western blacknose dace ( Rhinichthys obtusus ) along swimming pathlines in an experimental flume that was fitted with protruding bricks.…”
Section: Introductionmentioning
confidence: 99%
“…Agencies worldwide have developed guidelines for improving waterway connectivity at road crossings such as culverts (King & Torre, ), often based on learnings from other fish passage facilities (Duguay, Lacey, & Castro‐Santos, ). However, only a few acknowledge the potential effects of light on passage (Stuart, Berghuis, Long, & Mallen‐Cooper, ), or suggest mitigation options (Boubee et al, ; Cotterell, ).…”
Section: Potential Mitigation Optionsmentioning
confidence: 99%